Journal of basic microbiology (Akademie-Verlag, 1985)
"International journal on morphology, physiology, genetics, and ecology of microorganisms," 1985- ; "An international journal of biochemistry, physiology, genetics, morphology, and ecology of microorganisms," <2005->